Strong Back/Strong Mind: Mutually Exclusive? - Kellenberger, Rosemary C. (My University, 1986)
Those who object to the NCAA's Proposition 48, which was passed for the purpose of making sure that athletes do not participate in athletics the first year unless they are properly prepared for college work, appear to be doing a disservice to the athletes. They seem to imply that athletes are unable to demonstrate ability, especially the black athletes. Though some black athletes do tend to score lower on admissions tests than some white athletes, the facts do not prove that athletes, black or white, as a group, are any less able, potentially, than any other group. This article includes a brief literature review and author commentary.
Keywords: race; academic predictors; at-risk